Monitoring and evaluation of literacy programmes in Nigeria (2018)
Monitoring and evaluation is very important in keeping record of the successful implementation of any Programme, process or project. Literacy Programme as a crucial aspect of adult education needs to be monitored and evaluated in order to measure the achievement of desired results and set out objectives. Although the formal System of education has enjoyed a great level of monitoring and evaluation, this has not been properly implemented in the non-formal sector, especially for literacy programmes. Even when such evaluative processes are set in place, they merely emphasize the physical facilities while leaving out the other aspects of the evaluation process such as the facilitators’ inputs, learners’ performance and other things. Other challenges of evaluating literacy programmes in Nigeria include inadequate training of evaluation experts and lack of national benchmark for evaluation. This paper seeks to advocate for an all-encompassing forms of the evaluation of literacy programmes to achieve continuous successful outcomes of the desired objectives of the literacy programmes. It also suggests regular capacity building and training for evaluation officers as well as the setting of a national benchmark for evaluation of literacy programmes